Learners' Perceptions and Undergraduate Foreign Language Courses at a Colombian Public University - Ana Clara Sánchez Solarte; Gabriel Vicente Obando Guerrero; Diana Ibarra Santacruz (Asociación Colombiana de Profesores de Ingles, 2017)
This article reports the results of a study whose goal was to determine the views of undergraduate students regarding the English as a foreign language courses they must take as a requirement for graduation at a public university in Colombia. One hundred and thirty students from 10 undergraduate programs were surveyed and their responses were classified and analyzed. The findings indicate that learners are satisfied with the way foreign language courses are currently conducted. However, some aspects need further consideration and improvement. These suggestions are analyzed in this article.